2022
DOI: 10.1038/s41598-022-12049-z
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan polysulfate induces low-level persistent prion infection keeping measurable seeding activity without PrP-res detection in Fukuoka-1 infected cell cultures

Abstract: Each prion strain has its own characteristics and the efficacy of anti-prion drugs varies. Screening of prion disease therapeutics is typically evaluated by measuring amounts of protease-resistant prion protein (PrP-res). However, it remains unclear whether such measurements correlate with seeding activity, which is evaluated by real-time quaking-induced conversion (RT-QuIC). In this study, the effects of anti-prion compounds pentosan polysulfate (PPS), Congo red, and alprenolol were measured in N2a58 cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…However, in our previous study, PrP microspheres were not observed in the brains of patients with any other prion diseases treated with PPS [ 20 ]. A recent study has described varying effects of PPS on the amount and seeding activity of PrP res between each prion strain [ 41 ]. Thus, the effects of PPS treatments noted in the present study may be limited to V180I gCJD because of its specific prion strain.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our previous study, PrP microspheres were not observed in the brains of patients with any other prion diseases treated with PPS [ 20 ]. A recent study has described varying effects of PPS on the amount and seeding activity of PrP res between each prion strain [ 41 ]. Thus, the effects of PPS treatments noted in the present study may be limited to V180I gCJD because of its specific prion strain.…”
Section: Discussionmentioning
confidence: 99%
“…The murine neuroblastoma cell line N2a22L has been utilized, in which the murine scrapie prion 22L strain is expressed, leading to the sustained production of Proteinase K (PK) resistance protein, PrP Sc [ 54 ]. The N2a22L cell line has been widely used over the years as the most reliable model for the study of PrP Sc aggregation [ 18 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. Cells were cultured in Opti-MEM (51985042, Invitrogen Waltham, MA, USA) supplemented with 10% Fetal Bovine Serum (FBS) under a 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The murine neuroblastoma cell line N2a22L has been utilized, in which the murine scrapie prion 22L strain is expressed, leading to the sustained production of Proteinase K (PK) resistance protein, PrP Sc [54]. The N2a22L cell line has been widely used over the years as the most reliable model for the study of PrP Sc aggregation [18,[55][56][57][58][59][60][61][62][63][64]. Cells were cultured in Opti-MEM (51985042, Invitrogen Waltham, MA, USA) supplemented with 10% Fetal Bovine Serum (FBS) under a 5% CO 2 at 37 • C. Oenin (0911S, Extrasynthese Genay, France) and Myrtillin (0938S, Extrasynthese Genay, France) were dissolved in dimethyl sulfoxide (DMSO).…”
Section: Cell Culture and Ld 50 Estimationmentioning
confidence: 99%